Theoretical Approach of Growth Poles and Export Base Theories in Economic Development of Mozambique - Isaque Manteiga Joaquim; Raitone Armando; Elzira Tundumula (Cita Konsultindo Research Center, 2022)
Abstract Development theories have been used to guide the destinies of economies around the world. Among them are the theories of development poles that gained ground in the period 1960-1970, and then, having observed their decline from the second half of the 1970s. Since that period, these theories seem to be so dormant at the academic level as well as at the political level. With a view to recovering the theoretical framework of regional development theories, the pole of growth and export-based theories, as well as bringing their framework to economic and Mozambican development in particular, the research interest in the proposed theme emerged. For the study, a descriptive research was carried out based on theoretical contexts or approach made to the growth pole theories and the export-based theories, emphasizing their evolution over time and the possibilities of complementarity between them. The research used books and articles to review the literature and allowed separating models suggested by different authors, and situating the contribution of the regional development theories in Mozambique. One of the study's conclusions indicates that the country has not clearly adopted the poles of development strategies. However, given that the country has regional asymmetries, it may be opportune to learn from the mistakes of others and adapt it to the socio-economic reality of regions with the potential to emerge as true growth poles. The country has large investments in the mining and energy sector where studies show that they contribute little to the local economy. Following this fact, one cannot think of growth poles, but rather of an economic base, where there may be several companies with polarization and diffusion effects. The application of investment models that create income leakage in the region should be avoided as much as possible. The income retained in the region will be maximized when the greatest possible number of local productive resources (capital and labor) and the consumption of local goods and services are used. The involvement of the local business community must be a priority.